Cisplatin adducts at DNA or RNA do not affect their cellular isolation efficiencies using column-based kits or manual Trizol-based purification methods - Sandu, Ketaki; Theile, Dirk (Toxicology in vitro, 2026)
In experimental toxicology, evaluating cisplatin adducts at DNA or RNA is often required but can be complicated by methodological aspects. For instance, the cross-linking might affect the nucleic acid isolation efficiencies, which in turn can be influenced by the purification approach. Two cancer cell lines were cisplatin treated and DNA/RNA were isolated using manual Trizol-based protocols or column-based kits. Platinum levels at DNA/RNA were evaluated by atomic absorption spectroscopy. For RNA, the manual purification yielded higher concentrations than the kit for both cisplatin-treated and non-treated samples. RNA platination was identical for both isolation approaches. For DNA, the manual method can yield lower concentrations from cisplatin-treated cells, likely reflecting diminished solubility of cross-linked DNA. DNA platination levels again were identical with both isolation methods. Because DNA isolation is less efficient than RNA isolation, platinum-DNA adduct quantification is difficult when DNA yields are low or cells were exposed to low cisplatin concentrations. However, DNA platination can be estimated by the platination degree of RNA because platination of both nucleic acids agreed well and RNA was always isolated very efficiently. In summary: First, manual purification and column-based kits can yield unequal nucleic acid concentrations, and RNA is more efficiently purified than DNA. Second, column-based kits remain practical because platination does not affect isolation efficiency. Third, when DNA platination is not quantifiable (low yield, small sample volumes), RNA platination is a good proxy.